The Key Factors of Project-Based Learning Implementation On Higher Education: A Discourse Analysis Point of View - Muthia Damaiyanti; Desi Yulastri; Martini Martini; Edwar Kemal; Song Doo Jin (Universitas PGRI Sumatera Barat, 2024)
It is an essential factor that using a suitable learning model will enhance the learning outcomes for students. Project Based Learning (PJBL) is cosidered one of the learning model that guide the student to study inside the classroom and on the industrial world. The students learn theoritically and practically. This research was to find out the strength and weakness of PJBL during teaching and learning inside and outside of the classroom. It used qualitative research by using descriptive design. Data were collected by using interview question using semi structure interview and documentation. Data were analyzed by using theory of Miles & Huberman and Mc Carthy about discourse analysis. There were 71 students becoming the sample of the research from Politeknik Negeri Padang. After conducting the research, it is found some strengths and weaknesses of the PJBL for teaching and learning. PJBL. The strengths are for example: improving the student motivation, making the student to be diligent and challenging, being able to solve the problem, increasing the student collaboration and cooperation, teaching the student to make decision and conceptual framework, and how to work on the field. For the weakness are for example: taking much time and money, difficult to collect the information and best decision, do not make all student creative and innovative, and needing sufficient facilities and technologies to do the project.